Whose association is it? three MEFESZ in history of Hungary - Jancsák Csaba (Belvedere Meridionale, 2021)
MEFESZ (Association of University and College Students, AHUCS), which is considered to have been the spark of the 1956 Hungarian Revolution, was founded at the University of Szeged on 16 October 1956. The acronym (MEFESZ) appeared three times in the Hungarian history of the second half of the 20th century (in 1945, 1948, and 1956), and all three of them were youth and education organisations. The few years of the existence of each ‘MEFESZ’ has many lessons to teach. The three organisations, abbreviated identically but different in long forms of their names, each had different objectives and roles. In this paper, we show that the 1956 AHUCS (the third MEFESZ) was not a successor to either of the earlier organisations: the first MEFESZ of the period of the “tentative democracy” (1945–1948) and the second MEFESZ (in the first period of the communist dictatorship, 1948–1950). The precursor of the 1956 revolution (MEFESZ3 , AHUCS) was a new grassroots initiative, grounded in democratic principles in its aims, programs, and missions. The 1956 AHUCS organisation was not an umbrella organisation of student associations like the first MEFESZ organisation. The founders of the 1956 AHUCS were deliberate in not seeking to become the sole, unified organisation of university youth (like MEFESZ).